Пародийное в авторской песне - Osiewicz, Bartosz (Studia Rossica Posnaniensia, 2014)
In this article parody is analyzed as a type of intertextuality. A reader can only understand an artistic text which is a parody when he/she notices the contrast between its subject matter and form. Parody appears in Aleksandr Galich’s and Vladimir Vysotsky‘s author’s songs on different structural levels. Both poets purposefully chose the material to initiate a parodic game. The former prefers to interact with an elitist listener who comprehends the multi-level textuality of his works, while the latter refers to well-known literary texts.